MODERN-DAY SOLUTIONS FOR MODERN-DAY GLOBALISATION: PROPOSALS FOR CURBING IMPORTED ANTI-COMPETITIVE BEHAVIOUR (EU and comparative law issues and challenges series (ECLIC), 2024)
Cross-border conduct, such as cross-border cartels, export cartels, and abuse of dominance by multinational corporations, undertaken by firms in developed economies, can affect the economies of developing countries. This paper argues that such anti-competitive behaviour can only be curbed through the cooperation of the competition agencies of developing countries. Through looking at the harms of such conduct and assessing past and possible future solutions, this paper finds that creating a global competition law is not the only solution to this problem, but rather that plurilateral (or regional) and bilateral cooperation can be equally effective. Further, it finds that regional cooperation is not only effective in its own right, but also as tool to eventually reach an effective form of multilateral cooperation. Accordingly, it makes suggestions pertaining to international law instruments that can be used to limit cross-border anti-competitive conduct, the content of regional and bilateral agreements, and the role of international organizations in soft cooperation.